Need of standard materials for career education for primary school: teachers’ perspectives - Abdul Ghafar, Nurul Nadia; Mohamad Yusop, Yusni; Nor Zainudin, Zaida; Wan Othman, Wan Norhayati (Karadeniz Technical University, 2021)
Career education at an early stage of a young adult plays an important role in linking academic knowledge and an individual purpose of life, as well their self-development and motivation. This study aims to examine the need of standard materials for career education for primary school from the views of guidance and counselling teachers. The design of this study is a quantitative study. The sample consist of 131 guidance and counselling teachers working in Klang, Valley. Data was collected through a questionnaires and distributed to respondents. The data has been analysed using the Social Science Statistic Package (SPSS). The results found that 92.4% majority of respondents agreed for standard materials regarding career education to be distributed to counsellors in schools, and they chose modules, reference books and career dictionaries as the required career education materials. The discussion and implication for future research are provided.